Breast (females) and liver cancers in West Africa : temporal trends and evaluation of risk factors in the Gambia and Mali - (:unkn) unknown (My University, 2011)
In Sub-Saharan Africa, the exact burden of cancer remains largely unknown and understudied. The Gambia and Mali are among the few African countries with operational population-based cancer registries. Data from 1988 to 2006 for the Gambia and from 1987 to 2009 for Bamako-Mali were used to analyze the incidence rates according to age, sex and ethnicity and to characterize the profile of women with breast and liver cancers. The data were arbitrarily divided into two periods, 1988-1997 and 1998-2006 for the Gambia and 1987-1997, 1998-2009 for Bamako- Mali. In addition to this, a case-control study evaluating the risk factors associated with the reproductive life of women with breast cancer was conducted in Mali. In both countries, breast cancer in women is characterized by a predominance of premenopausal cancers. These women are mostly parous with a median age at diagnosis in the age group 40-45 years. The case-control study showed a significant association between late age at menarche and increased risk of developing breast cancer in pre-menopausal women against a decrease in risk among post menopausal women. Concerning liver cancer, while the incidence rate was relatively stable among males in the Gambia, it was increasing among females of this country. In contrary, in Mali, a gradual decline and homogeneous in the incidence of liver cancer was observed over the years and for both sexes. Further studies are needed to characterize the biological profile of breast cancer and risk factors associated with it, but also to assess the role of obesity and exposure to aflatoxin B1 in order to understand the trends observed in liver cancer in West Africa
Keywords: African Research